DISKURSUS KRITIK MATAN; Tashih Isnad terhadap Kontroversi Riwayat Rasulullah SAW Menyalatkan Ibn Ubay - Muhamad Ridwan Nurrohman (Diroyah : Jurnal Studi Ilmu Hadis, 2019)
This paper aims to examine the validity of the traditions relating to the events of the Prophet Muhammad prayer for Ibn Ubay. After doing the research it was found the conclusion that the histories related to the controversial event, all of them are Ṣaḥīḥ (authentic). Both the narrations which state that the Prophet prayed for Ibn Ubay, as well as narrations that "allegedly" rejected the truth of the event. Even though at-Thahawi considered that the history which stated that the Prophet prayed for Ibn Ubay was marjuh (Ḍaʻīf). Because it is contradicted with QS. At-Taubah: 80, and also other histories.